Concurrent Aerobic and Resistance Training Has Anti-Inflammatory Effects and Increases Both Plasma and Leukocyte Levels of IGF-1 in Late Middle-Aged Type 2 Diabetic Patients. (21st June 2017) - Annibalini, Giosuè; Lucertini, Francesco; Agostini, Deborah; Vallorani, Luciana; Gioacchini, Annamaria; Barbieri, Elena; Guescini, Michele; Casadei, Lucia; Passalia, Annunziata; Del Sal, Marta; Piccoli, Giovanni; Andreani, Mauro; et al.
Abstract : Type 2 diabetes (T2D) is an age-related chronic disease associated with metabolic dysregulation, chronic inflammation, and activation of peripheral blood mononuclear cells (PBMC). The aim of this study was to assess the effects of a concurrent exercise training program on inflammatory status and metabolic parameters of T2D patients. Sixteen male patients (age range 55–70) were randomly assigned to an intervention group (n = 8 ), which underwent a concurrent aerobic and resistance training program (3 times a week; 16 weeks), or to a control group, which followed physicians' usual diabetes care advices. Training intervention significantly improved patients' body composition, blood pressure, total cholesterol, and overall fitness level. After training, plasma levels of adipokines leptin (−33.9%) and RBP4 (−21.3%), and proinflammatory markers IL-6 (−25.3%), TNF- α (−19.8%) and MCP-1 (−15.3%) decreased, whereas anabolic hormone IGF-1 level increased (+16.4%). All improvements were significantly greater than those of control patients. Plasma proteomic profile of exercised patients showed a reduction of immunoglobulin K light chain and fibrinogen as well. Training also induced a modulation of IL-6, IGF-1, and IGFBP-3 mRNAs in the PBMCs. These findings confirm that concurrent aerobic and resistance training improves T2D-related metabolic abnormalities and has the potential to reduce the deleterious health effects of diabetes-related inflammation.